PROSTHENHYSTERA OBESA (DIESING, 1850) (DIGENEA, CALLODISTOMIDAE) IN THE SÃO FRANCISCO RIVER BASIN, BRAZIL: NEW HOST RECORDS AND THEIR ECOLOGICAL PARAMETERS - Nascimento Martins, Amanda (2012)
Prosthenhystera obesa (Diesing, 1850) (Digenea, Callodistomidae), parasitizes the gall bladder of freshwater fish and was first found in Leporinus reinhardti Lütken, 1875 (Characiformes, Anostomidae) and Pimelodus pohli Ribeiro & Lucena, 2006 (Siluriformes, Pimelodidae). These omnivorous fish were collected in the upper São Francisco River, Minas Gerais, Brazil. prevalence (%) and mean abundance of P. obesa were 1.58% and 0.02 ± 0.127 in L. reinhardti, and 3.85% and 0.04 ± 0.196 in P. pohli, respectively. Prosthenhystera obesa has already been reported in a carnivorous characin Salminus franciscanus Lima & Britski, 2007 and in an omnivorous pimelodid Pimelodus maculatus Lacepède, 1803 both in the São Francisco River, but their ecological parameters are here presented for the first time together with the data for L. reinhardti and P. pohli, two new hosts in the Neotropical Region. The ecological descriptors of P. obesa were similar, i. e., they were low in all fish of the São Francisco River and also in most fish from different hydrographic basins in accordance to literature review. It is noteworthy that despite the considerable morphometric variability, pregnant adult specimens of P. obesa occurred mainly in characin fish, especially ichthyophagous, top carnivores.